Yield Management Strategy in Increasing Room Occupancy in The New Normal Era - Ni Luh Gde Vania Pradina; Ida Ayu Elistyawati; Ni Nyoman Sri Astuti; I Gede Mudana (The Postgraduate School of Tourism Sahid Polytechnic, 2023)
Purpose: The purpose of this study is to find out what are strategies in increasing the occupancy rate of the new normal era at The Westin Resort & Spa Ubud, Bali and to determine the yield management strategy in increasing occupancy rates in the new normal era at The Westin Resort & Spa Ubud, Bali. Research methods: The types of data used are qualitative and quantitative data. Data collection methods used in this study were observation, interviews, questionnaires, and literature study. The data analysis technique used is descriptive qualitative and quantitative methods. This study uses a marketing mix approach with a SWOT analysis using the 7P indicator. Results and discussion: Yield management strategies that can be used to increase room occupancy are expanding market share and working partners with travel agents, increasing promotions based on information technology and utilizing social media, strengthening local culture on products to be sold, providing valet parking for guests, providing technology application training to staff regularly to improve staff quality and performance, creating and developing products according to current trends. Implication: The Westin Resort & Spa Ubud, Bali is in a growth stage. Keywords: yield management, room occupancy, new normal, SWOT.